Inequality decompositions: A reconciliation - Frank A. Cowell; Carlo V. Fiorio (Luxembourg Income Study (LIS), 2009)
We show how classic source-decomposition and subgroup-decomposition methods can be reconciled with regression methodology used in the recent literature. We also highlight some pitfalls that arise from uncritical use of the regression approach. The LIS database is used to compare the approaches using an analysis of the changing contributions to inequality in the United States and Finland.
Keywords: D63; 330; inequality; decomposition; Soziale Ungleichheit; Messung; Finnland; USA